PENGARUH GAYA HIDUP, CITRA MEREK, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION (Studi Empiris Pada Konsumen Districtside Store di Semarang) - Dimas Prayudianto, 13.05.51.0076; Widyasari, Suzy (Students Journal of Economic and Management, 2017)
This purpose of this study was to analysis the effect of lifestyle, brand image, and percived price to purchasing decision of fashion product in Districtside Store Semarang. The population in this study were consumers who made a purchase of fashion products at Districtside Store Semarang. The number of samples studied were as many as 100 people were selected as respondents used purposive sampling technique. Data collection methods used in this study was questionnaire filled out by respondents. The analysis used in this study was multiple linear regression to examine the effect of partially each independent variable,there were lifestyle, brand image and perceived price to dependent variable that was purchasing decesion. The results of this study showed that lifestyle, brand image, and perceived price had a positive and significant effect on purchasing decisions at Districtside Store Semarang. Keyword: Lifestyle, Brand Image, Percived Price and Purchasing Decision